Digital transformation of the labour sphere: a comparative analysis of the indicators of Russia and Belarus - Titarenko, Larissa G.; Karapetyan, Ruben V. (Journal of the Belarusian State University. Sociology, 2021)
The article provides a comparative analysis of the indicators of development and dissemination of information and communication technologies in the field of labour, achieved in the Russian Federation and the Republic of Belarus in the process of digital transformation of the sphere of labour within the framework of state programs for the development of digitalisation in both countries. The purpose of the article is a comparative analysis of the effectiveness of digital transformation processes that determine changes in the social and labour sphere of the two countries. The goal is revealed by solving two main tasks – the analysis of state statistics data and the analysis of the results of sociological research conducted in this area. The authors proceed from the thesis of the duality of the processes of digitalisation of labour and show that they not only bring positive results, but also create new risks and threats to humanitarian security. Comparative analysis of statistics shows the success achieved by each country in the digital transformation of labour, reveals the trends of this process, while the results of sociological research reveal the negative consequences of the same processes (technostress, the growth of digital inequality, burnout of the employee). It is concluded that there is a need for a balanced approach to the further development of the digitalisation of labour and the development of social policy measures aimed at reducing potential risks to the working man.